UPAYA MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM DI INDONESIA DALAM MEWUJUDKAN PROGRAM SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Khaidir Fadil; Noor Isna Alfaien; Ahmad Mulyadi Kosim (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
The purpose of this research is to examine the importance of efforts to improve the quality of education in Indonesia, especially Islamic education, which is considered to be of poor quality. The research method used is a qualitative method with a literature review and a descriptive method is used. The data in this study were obtained from the results of literature reviews obtained from journals and articles. This study shows that the situation of education in Indonesia, especially Islamic education, is still at an alarming level. This shows the uneven quality of education between urban and rural communities, the lack of professionalism and capacity of the teaching staff, the hours of PAI which are limited to only 2 hours per week, followed by a teaching orientation that only focuses on students' cognitive aspects, as well as monotonous teaching methods which have an impact on the low quality of Islamic education in Indonesia. Therefore, special efforts and strategies are needed to improve the quality of Islamic education in Indonesia in order to realize the SDGs, namely quality, equitable education and lifelong learning opportunities for all ages. Build public trust in Islamic education, design curricula according to community needs, produce highly competitive graduates with tiered facilities and infrastructure, as well as increase and improve competitiveness through proven science and technology. Teachers and teaching staff, using a technology teaching environment, are using digital libraries.